Exploring Determinants of Adherence to Medical Regimens in Patients with Chronic Conditions Beyond Hypertension and Diabetes - Niraj PANDIT; Aneri AMIN; Ashka DESAI; Vedant BHATT; Ajay NIMMAGADDA; Yagna PANDIT (Modern Medicine)
Chronic diseases are significantly increasing globally and increasing premature deaths among population. CDC has defined chronic diseases are the conditions that last 1 year or more and require ongoing medical support or limit the daily activities or both. Diabetes and hypertension are popular chronic diseases. But there are many others are also now increasing. The current study was conducted to find out the prevalence of noncompliance among chronic diseases like thyroid diseases, Asthma, COPD, Orthopedic problems and epilepsy. Also to understand the determinants factors among them. It was a hospital based cross sectional study. The sample size was calculated and it was 36 for each disease. Total 40 study participants of each disease were included. It was randomly selected the individuals diagnosed with the mentioned chronic diseases who have been diagnosed and on treatment for more than 3 years from hospital. Result: A total of 200 patients participated in the study. The study included 40 patients from each chronic disease that is thyroid disorders, COPD, Orthopedic problems, Asthma and Epilepsy. The rural population comprised 69% of the total study group. The prevalence of medical noncompliance was found in 56.5% of all the patients. People having the disease for longer period of time were more non-compliant. The study revealed that family support and regular follow up with doctor are two important determinate factors which has positive impact on compliance. Conclusion: Noncompliance to medication regimen among chronic disease patients is an important issue for public health consideration. This current study recorded an overall noncompliance level of 57.5%. The factors identified as contributing to medication noncompliance in this study were regular follow-ups, family support, adequate knowledge regarding their disease and importance of taking medication with or without symptoms.